Pengaruh Pembelajaran Awareness Training Berbasis Kognitif Sosial (ATEKSI) Terhadap Konsep Diri Siswa Kelas V di SD Negeri Krogowanan - Rasidi Rasidi; Ari Suryawan (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2023)
Students' self-concept is a view of themselves that represents experience and information so far and has an impact on the steps of success in living life. Not all students at SD N Krogowanan have a positive self-concept, so intervention is needed, one of which is through the implementation of learning according to the problems experienced by students about the need for learning that builds self-awareness and is socially oriented. The research objective was to determine the effect of the social cognitive-based Awareness Training learning model (ATEKSI) on students' self-concept. Research with a quantitative approach, pre-experimental design, using the type of one group pretest-posttest design. The research sample was 31 students of class V with a sampling technique, namely total sampling. The main instrument is a questionnaire whose indicators include: self-image, self-ideal, self-esteem, self-role, self-identity, observation instruments (support). Data analysis techniques using the t test with paired sample t test. The results showed that the mean pretest self-concept score was 81 with a percentage of 63% and posttest with a score of 117 with a percentage of 91%. Based on the results of the t test, it was obtained t count 21,528 > t table 2,042. Significance results were obtained sig 0.00 <0.05, this means that there is a significant difference and influence in the application of social cognitive-based Awareness Training (ATEKSI) learning on the self-concept of fifth grade students at SD Negeri Krogowanan.